ANALISIS DAN PEMODELAN PROSES BISNIS UMKM KAFFAH PARFUME MENGGUNAKAN BPMN UNTUK MENINGKATKAN EFISIENSI OPERASIONAL - Silvi Rahmawati; Abdul Azis Nasution; Mira Fathila Sari; Harsya Haryo Prastya; Indah Riski Panjaitan; Ari Sahputra; Rizky Khaliq; Ika Yusnita Sari (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2025)
This study analyzes and models the business processes of UMKM Kaffah Parfume using the Business Process Model and Notation (BPMN) method. The analyzed processes include ordering, raw material procurement, and product delivery. Business process modeling was carried out to represent operational activities and identify inefficiencies affecting organizational performance. Simulation using Bizagi Modeler indicates several areas requiring improvement, particularly in raw material stock management, delivery coordination, and order documentation. The proposed process improvements are expected to enhance operational efficiency and reduce delivery time, thereby supporting better customer satisfaction and overall business management.